Withholding Taxes or Information Exchange: The Taxation of International Interest Flows. - Harry Huizinga; Søren Bo Nielsen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2000)
This paper considers withholding taxes and information exchange as alternative means to tax international interest income. For each regime, we consider the maximum level of taxation of foreign-source income that can be sustained as the equilibrium of a repeated game. The best regime is the one that brings the level of taxation in the repeated game closest to the cooperative level of interest taxation. Sustainable levels of taxation in either regime depend on the importance of bank profits and on the marginal cost of public funds, among other things. Simulations with the model illustrate the choice between withholding taxes and information exchange. An explicit possibility is the emergence of a mixed regime, with one country imposing a withholding tax and the other country providing information. The basic model is extended to allow for size differences between the two countries and to incorporate a third, outside country.
Keywords: 330